The principle of resistive sensing - Arshad, Atika; Tasnim, Rumana; Khan, Sheroz; Alam, A. H. M. Zahirul (IIUM Press, 2011)
A resistive sensor is a device that is able to sense any change occurred in the parameter of interest due to the change in resistance. Resistive displacement transducer is one of the mostly used transducers. It uses a resistive element with a sliding contact attached to the object the position of which is being monitored